Impact of Lean Accounting on Value of the Company at the Jordanian Industrial Companies - Shehadeh, Mohammad Ahmad; Al-Beshtawi, Suleiman Hussein (International Review of Management and Marketing, 2023)
The purpose of this study was to determine how lean accounting affected the value of the company in Jordanian industrial companies. The researchers used a descriptive-analytical approach to examine study data collected through a questionnaire and from the annual financial reports of the (52) Jordanian industrial companies listed on the Amman Stock Exchange during the period from 2017 to 2021. The study brought up a number of findings, the most important of which are: the availability of an impact of lean accounting tools in enhancing the company's value in Jordanian industrial public shareholding companies, with a high level of relative importance. The study provided a number of recommendations, the most important of which was that Jordanian industrial companies' management creates well-structured plans and implements effective strategies to support increasing the value of the company and achieving excellence and prosperity.